Speak to us of love : selected talks by Osho on Kahlil Gibran's "The Prophet" - Osho, 1931-1990 (Osho Media International ; Distributed by Publishers Group Worldwide, 2013)
Examines mystical aspects of Khalil Gibran's best-known work, "The Prophet," and explains that it demonstrates how possessiveness can destroy love in the home, at work, and in other aspects of life.